High-Payload Nanosuspension of Centella asiatica Extract for Improved Skin Delivery with No Irritation - Kim EA (Dove Medical Press, 2021)
Eun A Kim, Jun Soo Park, Min Seop Kim, Min Young Jeong, Hyun Jin Park, Jun Hyuk Choi, Jae Hee Seo, Yong Seok Choi, Myung Joo Kang College of Pharmacy, Dankook University, Cheonan, Chungnam, 330-714, KoreaCorrespondence: Myung Joo KangCollege of Pharmacy, Dankook University, 119 Dandae-ro, Dongnam-gu, Cheonan, 330-714, KoreaTel +82 41 550 1446Fax +82 41 550 7899. Email kangmj@dankook.ac.krBackground: The titrated extract of Centella asiatica (CA) has received much attention as a cosmeceutical ingredient owing to its anti-wrinkle effect. However, due to the low solubility and high molecular weight of pharmacologically active constituents, including asiatic acid (AA), madecassic acid (MA), and asiaticoside (AS), it is challenging to fabricate high-payload topical preparations of CA with satisfactory skin absorption profiles.Purpose: This study aimed to design a high-payload topical preparation of CA using nanocrystallization technique and to evaluate its skin absorption profile and local tolerability.Methods: High-payload nanocrystal suspensions (NSs) were prepared using lab-scale bead-milling technology, by adjusting the type and amount of suspending agent, CA content, type of vehicle, and milling speed. CA-loaded NSs were characterized in terms of morphology, particle size, crystallinity, and in vitro dissolution pattern. Skin absorption of CA nanocrystals was evaluated using a vertical Franz diffusion cell mounted with porcine skin. In vivo skin irritation following topical application of high-payload NS was assessed in normal rats.Results: The optimized NS system, composed of 10% (w/v) CA, 0.5% polyvinylpyrrolidone (PVP) K30 as steric stabilizer, and 89.5% of distilled water, was characterized as follows: spherical or elliptical in shape, 200 nm in size, with low crystallinity. The in vitro dissolution of AA or MA from NSs was markedly faster compared to raw material, under sink condition. Penetration of AA, MA, and AS in the porcine skin was markedly elevated using the high-payload NS formula, providing 5-, 4-, and 4.5-fold higher accumulation in skin layer, compared to that of the marketed cream formula (CA 1%, Madeca cream). Moreover, topical application of high-payload NS was tolerable, showing neither erythema nor oedema in normal rats.Conclusion: The novel NS system is expected to be a virtuous approach for offering a better skin absorption of CA, without using an excess quantity of solubilizers.Keywords: Centella asiatica, asiatic acid, madecassic acid, asiaticoside, nanocrystal suspension, bead-milling, dissolution, skin absorption, skin irritation